Pemberdayaan Potensi Lokal melalui Edukasi Profesi (Sumber Daya Manusia) dan Bahasa Asing pada Sekolah Dasar Negeri 031 Desa Sidorejo Penajam Paser Utara - Dian Saripujiana; Amelia Ayu Syafitri; Widya Rahma Sarita (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service program was implemented with the aim of optimizing the local potential of Sidorejo Village through professional education activities as a form of human resource development, as well as foreign language learning for students of State Elementary School 031 Sidorejo Village, Penajam Paser Utara Regency. The main problems identified were the limited knowledge of students regarding local potential in their surrounding environment and the low mastery of contextual basic English vocabulary. The implementation of the program used an educational, participatory, and contextual approach through the utilization of interactive visual media, socialization activities, and direct mentoring for students. The materials provided included the introduction of various local professions, the instillation of basic leadership values, and the learning of simple vocabulary and sentences in English. The results of the program indicated an improvement in students' understanding of local professions, increased awareness of village potential, and the growth of students’ confidence in using basic English. This program is expected to become an alternative contextual learning model to support early human resource development based on local potential.